READING ENVIRONMENT AND FLUENT READING SKILLS - Mokhlaroyim Erdanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Reading skills, which are among the other language skills, play a vital role for an individual in adapting them into his daily life. Reading should not be interpreted as recognizing merely the letters, the word and articulating them. In addition to understanding what is written, being able to read fluently is also one of the skills that need to be developed in reading teaching. The aim of this research is to determine the role of the reading environment on fluent reading skills. 24 students who were enrolled in the third and fourth grades of a primary school in the center of Bartin participated in the study. The demographic features of the students such as gender, class, possession of technological tools (computer, tablet, smart phone, etc.), and duration of use of technological tools were identified using a personal information form. As a result , after giving a number of variation of texts suggestions were made to support the use of electronic media in schools and improve reading skills by supporting the use of technological tools.